Towards a Methodology of Wicked Problem Exploration through Concept Shifting and Tension Point Analysis. (30th October 2013) - Houghton, Luke; Tuffley, David
<x xml:space="preserve">Abstract</x> Synthesis is a creative and mysterious process in which a chaotic array of concepts, what might be called a mess, is cognitively 'engaged' with a problem domain to produce as many interpretations as can validly be derived for effective decision‐making purposes. The benefits of engaging concepts into a mess are that it allows the problem to be viewed through multiple lenses simultaneously, which affords a holistic vantage point for richer problem interpretation. By deliberately shifting the underlying concept held by actors and provoking the movement of concepts, better interpretations might lead to more useful decision making. Although research has discussed the possibility of using synthesis through case studies, we argue that there is a need to formally develop methodologies in this area for the purpose of fostering and solving complex problems. To demonstrate this, we provide a speculative case study to illustrate how this approach may be usefully applied. Copyright © 2013 John Wiley & Sons, Ltd.